PRAKTIK PEKERJAAN SOSIAL BERBASIS KOMUNITAS PEDULI ANAK JALANAN DI KOTA BEKASI - Angger Zahrotun Nur Hidayah; Anisa Herawati; Latifah Retno Sari; Ririn Novia Zulfatur Rohman; Sisya Nabila Mukriyati (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
The phenomenon of street children often occurs in cities in Indonesia, not only in big cities, in smallcities there are street children as well. One example is the phenomenon of street children in Bekasi City.The problem of street children has a huge impact on the survival and development of these children.Until now, the problem of street children is still a hot issue to be discussed. The purpose of this researchis to find out the practice of community-based social workers who care about the education of streetchildren (Koppaja) in the city of Bekasi. The method used in this research is qualitative method. Theresults of this study are the Koppaja community in collaboration with the Bekasi City Manpower Serviceto minimize and overcome these problems through various models andapproaches, and operate in linewith social work knowledge, values and skills. Koppaja emphasizes their priority on the education ofstreet children and the poor. Handling the problem of street children through programs in the practiceof community-based social work creates an opportunity for street children and the poor to face varioussituations in the future, especially in the field of education.